« A reality that almost amounts to illusion » - Martine Lambert-Charbonnier (Sillages Critiques)
Walter Pater’s description of Mona Lisa in The Renaissance (1873) turns the famous picture – which as a portrait gives the faithful image of a real person – into a symbol of human aspirations. Considering the painter as a rival of nature, Leonardo da Vinci creates beauty and life in his art, while Mona Lisa embodies the ideal of the Renaissance with its emphasis on experience and the senses which fin-de-siècle writers find so akin to the modern spirit. The transition from mimesis to symbolism in the painting is conveyed by the colour perspective, in particular the sfumato, the interplay of light and shadow introduced by Leonardo which seems to veil the picture in darkness. Thus “behind the veil” the painter expresses his quest for harmony and fertility in the cosmos, a meaning decadent writers are keen to subvert to make the picture a symbol of corruption and passion.